Twenty Years of Existence of Damar Kurung Gresik: Analysis Of Tajfel&Turner’s Identity Theory - Camelia, Ika Aanggun (Jurnal Indonesia Sosial Sains, 2024)
Damar Kurung is a Gresik Visual cultural heritage popularised by Masmundari since it was raised by cultural experts and exhibited in national galleries. In 2017, Damar Kurung was officially recognised by the government as an intangible visual culture. This will allow the research to study Damar Kurung further, which is now used as one of Gersik's cultural identities. The research method used is a case study that focuses on journal outputs and social media track records as the primary data and an interview method to confirm the analysis results; the research object is a journal with the theme of Damar Kurung from 2004-2024. The theory used in dissecting the data is the Tajfel and Turner identity theory, studied from the employer branding perspective. This research will find cultural value for psychological, functional, and economic benefits. In addition, it also explains how commodities help to raise their self-esteem. The usefulness of the commodity to the environment. Community acceptance in the damar kurung and the last. Moreover, the evaluation of the group tries to determine and use it as a reference material for other groups, specifically through social comparisons in the form of attribute values or characteristics. This research will improve understanding of how cultural heritage can be preserved and promoted as an important part of regional identity.